Study on deformation characteristics and energy evolution of coal under different loading rates - Peng JIN; Ying LIU; Junjun FENG; Shigeng LI; Yuanfang QU (Meikuang Anquan, 2024)
The digital image correlation (DIC) technology was used to investigate the evolution law of the coal surface strain field under different loading rates and to analyze the influence of loading rate on the evolution of the deformation field, deformation localization, and surface deformation energy density. The experimental results indicate that the higher the loading rate is, the more complete the final failure mode of the coal body, and the failure mode of the coal body also transitions from shear failure to tensile failure; the loading rates of different magnitudes also affect the localization time of coal deformation. The higher the loading rate is, the greater the proportion of the initiation time of coal deformation localization to the overall failure time. The higher the loading rate is, the more obvious the growth trend of deformation energy density before deformation localization, and the more energy accumulates in the surface deformation localization area; the qreater the stress at the start time of deformation localization.